Performance of a membrane fabricated from high-density polyethylene waste for dye separation in water. Issue 12 (8th March 2023) - Zulfiani, Utari; Junaidi, Afdhal; Nareswari, Cininta; Ali, Badrut Tamam Ibnu; Jaafar, Juhana; Widyanto, Alvin Rahmad; Saiful; Dharma, Hadi Nugraha Cipta; Widiastuti, Nurul
Abstract : Industrial growth can have a good impact on a country's economic growth, but it can also cause environmental problems, including water pollution. Abstract : Industrial growth can have a good impact on a country's economic growth, but it can also cause environmental problems, including water pollution. About 80% of industrial wastewater is discharged into the environment without treatment, of which 17–20% is dominated by dyes, such as methylene blue (MB) and methyl orange (MO) from the textile industry. Only about 5% of a textile dye is used in the dyeing process and the rest is discarded. This problem, of course, requires special handling considering the harmful effects to health. On the other hand, the abundance of plastic waste is increasing by 14% or 85 000 tons per year. This problem must be solved due to its film-forming properties. High-density polyethylene (HDPE) is one type of plastic used as a membrane material. Therefore, in this study, HDPE plastic waste was utilized as a membrane for dye removal. In this study, HDPE plastic waste was fabricated via a thermal-induced phase-separation method using mineral oil as a solvent at various concentrations of 8%, 10%, 13%, and 15% (w/w). All the membranes were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, and contact angle measurements. The results showed that the HDPE membrane at a concentration of 15% displayed the best performance compared to the others in terms of MB rejection. The negative charge (−36.9) of the HDPE membrane was more effective for cationic dye removal compared to the anionic dye. The flux and rejection of HDPE 15% for 100 ppm MB and MO removal were 2.71 and 4.93 L m −2 h −1, and 99.72% and 89.8%, respectively. The pure water flux of the membrane was 15.01 L m −2 h −1 and the tensile strength was 0.3435 MPa.